Cultural studies : le paradigme hallien - Marc Lenormand (Contextes)
The issue as to whether cultural studies are a method or offer any such thing is approached here through an examination of a series of texts penned by Stuart Hall between the early 1980s and early 1990s, in which he expounded a theoretical history of British cultural studies. Taken together, these texts constitute a significant attempt, by a key figure in the history of British cultural studies, at giving an account of the intellectual endeavour that took the shape of cultural studies. What comes out of Hall’s writings is not a sense of cultural studies as a unified or unifying method, but rather an insistence on methodological pluralism, a restless engagement with theory and a commitment to grafting academic work onto political work, all of which led to the continuous transformation of cultural studies as a project.